Early Marriage Phenomena in Pandemic Era at Luwu Utara, Indonesia - Husain, Wahyuni; Bahtiar, Bahtiar; Kahfi, Muhammad Ashabul; Indiyanto, Agus; Fatmawati, Fatmawati (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2024)
The impact of the Covid-19 pandemic has affected every aspect of life. Not only the decline in the economic situation, but it has also had an impact on the emergence of social problems such as the high rate of early marriage. Early marriage has been a scientific concern for a long time. However, scientific studies have not been able to reduce the rate of increase in the number of children marrying early. The loss of the rights of children who should receive proper education, play and the right to protection are forced to be “bound” in a marriage. The purpose of this article is to add references to solving the problem of early marriage which has been long problematic on an international, national and regional scale. This article discusses the objective conditions of early marriage during a pandemic and criticizes the implementation of strategies for preventing and handling cases of the early child marriage. The data in this study were taken from the main data in the form of in-depth interviews with competent informants. Additional data was taken from existing data at the related office in North Luwu Regency along with the news from online sites, became a reference in this article. This study establish that the number of early marriages has rising due to the widespread use of social networks and changes in daily activity patterns. For future studies, it is recommended to consider the determinant factors in different locations and in a wider scope.